Active responses of nanoparticle-polymer interface/interphase via the interfacial interaction redistribution. (1st April 2023) - Wang, Guotong; Wang, Ruijie; Wang, Chengyuan; Tang, Chun; Zhang, Faling
Highlights: A strain triggers the interaction redistribution and active interphase/face responses. Strain-dependent material properties are achieved for the stretched interphase. Highly nonlinear behavior with three statuses is found for the elongated interface. Physical parameters are defined for the interface subjected to general loadings. Abstract: Physical responses of nanoparticle (NP)-polymer interphase/interface to external stimulus are a topic of great interest in nanocomposites. Previously, the interphase was tacitly assumed to have passive responses with constant material properties during deformation while the interface was mainly studied under hydrostatic loadings. To explore the unique features of the interphase we used a full-atom molecular dynamics simulation to monitor the evolution of its mass density and atomic stress profiles during deformation. A cohesive zone model was then used to define the key parameters for the NP-polymer interaction, which enable one to study the responses of the interface without spherical symmetry and understand the unique behavior of the stretched interphase/interface. The conceptual change has been achieved showing that an external strain can redistribute the NP-polymer interaction to affect the high compression in the interphase, the physical origin of the interface confinement effect in the nanocomposite. This eventually triggers the active responses of the interphase leading to the apparent strain-dependence of the mass density and some other properties. The redistribution of the interfacial interaction also brings about the stable, metastable and unstable status of the stretched interface characterized by the strain-dependent modulus and interface debonding. Graphical abstract: Image, graphical abstract